1987
DOI: 10.1002/aja.1001800405
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serotonin‐immunoreactive paraneurons in the lower urinary tract of dogs

Abstract: Morphological and quantitative studies were made on serotonin-containing paraneurons throughout the lower urinary tract in male and female dogs. Using an anti-serotonin antiserum, the cells were consistently demonstrated to be dispersed in the epithelium from the vesico-urethral junction to the external urethral ostium. They occurred most frequently in the urethra proximal to the urogenital diaphragm in both sexes. The total number of the serotonin-immunoreactive cells in the urethra was estimated to be 36.2 X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 19 publications
2
37
1
3
Order By: Relevance
“…There are very few arguments in favor of the implication of peripheral 5-HT in ejaculation. Serotonergic neural fibers have been detected in prostate, seminal vesicle, vas deferens, and urethra in different species (Hanyu et al, 1987;Di Sant'Agnese et al, 1987). mRNAs for 5-HT1A, -1B, and -2C receptor subtypes were found in rat seminal vesicles and vas deferens (Kim and Paick, 2004), although their precise location (pre-or postsynaptic) is unknown.…”
Section: Pharmacology For the Treatment Of Premature Ejaculation 627mentioning
confidence: 99%
“…There are very few arguments in favor of the implication of peripheral 5-HT in ejaculation. Serotonergic neural fibers have been detected in prostate, seminal vesicle, vas deferens, and urethra in different species (Hanyu et al, 1987;Di Sant'Agnese et al, 1987). mRNAs for 5-HT1A, -1B, and -2C receptor subtypes were found in rat seminal vesicles and vas deferens (Kim and Paick, 2004), although their precise location (pre-or postsynaptic) is unknown.…”
Section: Pharmacology For the Treatment Of Premature Ejaculation 627mentioning
confidence: 99%
“…The peptide oxA has recently been found in NE cells of the cattle urethra (Russo et al, 2008), where 5-HT is widespread diffused. The amine, in fact, is the main product of the NE cells scattered along the urogenital tract of humans of both sexes (Fetissof et al, 1983), dog (Hanyu et al, 1987), and sheep (Vittoria et al, 1990). Furthermore, 5-HT and oxA have been found in Leydig cells of hamster (Frungieri et al, 1999) and rat (Barreiro et al, 2005) testis, where they regulate steroidogenesis through an antagonistic mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…HANYU et al (1987) reported the frequency of the occurrence of the serotonin-immunoreactive cells in the canine urethra of both sexes. The "clear cells" in the urethra comprise the cells to be categorized into paraneurons according to their cell-biological features.…”
Section: Endocrine Cellsmentioning
confidence: 99%